Servitization of Job Shop Scheduling Algorithms - LIU Sheng-hui; ZHANG Xing; ZHANG Shu-li; MA Chao (Journal of Harbin University of Science and Technology)
The scheduling algorithm resources are not yet fully shared betwwen manufacturing execution system, and it is difficult to efficiently select the appropriate scheduling algorithm for scheduling problem from the candidate scheduling resources. To resolve this issue, the servitization of job shop scheduling algorithm resource in cloud manufacturing was studied. Firstly, an OWLS based ontology data model and publication specification of